Chronic meningitis in Thailand: Clinical characteristics, laboratory data and outcome in patients with specific reference to tuberculosis and cryptococcosis - R. Helbok (2018)
The charts of 114 consecutive patients with chronic meningitis admitted to a general hospital in Bangkok, Thailand, between 1993 and 1999 were retrospectively reviewed. The most common causative agents were Cryptococcus neoformans (54%) and Mycobacterium tuberculosis (37%). HIV and other underlying diseases had a major impact on the presentation of chronic cryptococcal meningitis patients. Compared to HIV-negative cryptococcal meningitis patients (21%), HIV-positives (79%) had a significantly lower incidence of focal signs (p = 0.02), hydrocephalus (p = 0.03) and seizures (p = 0.001) during hospital stay, furthermore, a lower leucocyte level, a significantly higher glucose level (p = 0.02) and a lower protein level (p = 0.03) in the first cerebrospinal fluid examination. Of the 43 patients with chronic tuberculous meningitis, only 3 were HIV positive. Focal neurologic deficits were found more frequently in tuberculous meningitis patients (p = 0.001) when compared to cryptococcal meningitis patients without HIV. Cerebral infarction on cerebral CT was indicative of tuberculous meningitis. Cryptococcal meningitis patients with HIV infection had a worse outcome compared to non-AIDS patients. Advanced stage of the disease on admission, decreased level of consciousness prior to and on the admission day and raised intracranial pressure above 40 cm H2O at any given time were predictive of a poor outcome in tuberculous meningitis patients. Copyright © 2006 S. Karger AG.